Biosynthesis of silver nanoparticles using phyllanthus emblica fruit extract for antimicrobial application. (March 2020) - Renuka, R.; Devi, K. Renuka; Sivakami, M.; Thilagavathi, T.; Uthrakumar, R.; Kaviyarasu, K.
Abstract: Biological synthesis of metal nanoparticles is one of the effortless, cost - effective, environmental - friendly methods and scale down the handling of toxic chemicals. The silver nanoparticles were triumphantly synthesized from the silver nitrate solution through a greener route using Indian gooseberry ( phyllanthus emblica ) fruit extract and the prepared particles are of well-balanced shape and size. The stabilization and the bio-reduction of silver nanoparticles were described by adopting UV–vis spectrometry interprets the surface plasmon resonance peak at 449 nm. The functional groups of phyllanthus emblica fruit extract and the silver nanoparticles were diagnosed by using Fourier transform Infrared spectrum (FTIR). The crystalline nature of face-centered cubic (FCC) was examined by X-ray diffraction (XRD) and the crystalline size ranges between 19 nm to 45 nm with an average size 30 nm. Scanning electron microscope (SEM) witnessed the hexagonal shape of silver nanoparticles and Energy-dispersive X-ray spectroscope (EDX) assured the well-established fabrication of nanocrystalline silver element. The synthesized nanoparticle exhibits significant antibacterial effects and very clear zone of inhibition against Klebsiella pneumoniae and Staphylococcus aureus bacterias.